A comparison of pediatric basic life support self-led and instructor-led training among nurses. (February 2017) - Vestergaard, Lone D.; Løfgren, Bo; Jessen, Casper L.; Petersen, Christina B.; Wolff, Anne; Nielsen, Henrik V.; Krarup, Niels H.V.
Abstract : Objective: Pediatric cardiac arrest carries a poor prognosis. Basic life support improves survival. Studies on pediatric basic life support (PBLS) training are sparse. The aim of our study was to investigate the effect of self-training in PBLS. Participants and methods: We conducted a prospective controlled trial enrolling nurses from pediatric and maternity wards ( n =29 in each group). Self-training, including a manikin and access to a web-based video on PBLS, was compared with a 2-h instructor-led course. Two weeks after training, all participants were tested in a mock scenario of pediatric cardiac arrest. Fifteen parameters equivalent to the steps in the PBLS algorithm – for example, effective ventilations, effective chest compressions, calling for help, and correct sequence of actions, were evaluated and rated dichotomously (1=approved or 0=not approved). Results: No difference was observed in the baseline demographics between the self-training group and the instructor-led group. The participants in the self-training group accessed the website 2±1.5 times (mean±SD) and spent 41±25 min on the site. There was no significant difference between the two groups in the overall average score (10.5 in the self-training group vs. 10.0 in the instructor-led group, P =0.51) or in any of the 15 parameters. After the study, all participants felt that they had improved their skills and felt capable of performing PBLS. Conclusion: Self-training is not statistically different to instructor-led training in teaching PBLS. Self-evaluated confidence improved, but showed no difference between groups. PBLS may be disseminated through self-training.